2004
DOI: 10.1108/14635770410520302
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking as an action research process

Abstract: This study participates in the debate on advancing theoretical developments in the field of benchmarking processes. It suggests that approaching benchmarking as a research method helps to explicate the basis of benchmarking processes and at the same time offers tools for scientific research in this field. Adopting an interpretative, comparative concept analysis the study approaches benchmarking as an action research. The results indicate that benchmarking might be regarded as a special kind of action research;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 25 publications
1
30
0
1
Order By: Relevance
“…to improve practices, (2) the researcher's role, (3) how the processes take place and how they can be either adapted or created, (4) the phase of action research vs the phases of benchmarking. Kyro (2004) provides a review of benchmarking models and a classifications of benchmarking phases compared to action research. Kyro (2004) approaches the benchmarking process as a "two-cycle spiral, where the actual data collection phase is regarded as an action of the first cycle […] and at the same time is generic enough to be adopted for different forms of benchmarking"…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…to improve practices, (2) the researcher's role, (3) how the processes take place and how they can be either adapted or created, (4) the phase of action research vs the phases of benchmarking. Kyro (2004) provides a review of benchmarking models and a classifications of benchmarking phases compared to action research. Kyro (2004) approaches the benchmarking process as a "two-cycle spiral, where the actual data collection phase is regarded as an action of the first cycle […] and at the same time is generic enough to be adopted for different forms of benchmarking"…”
Section: Discussionmentioning
confidence: 99%
“…Measure the existing state of the subject to be benchmarked with respect to the critical success factors/indicator 13. Form a benchmarking team and identify a leader of the team to carry benchmarking study "Benchmarking as an action research process" (Kyro 2004) "Even though definitions vary between scholars, the aspects of evaluation and improvement by learning from others are embedded in the definitions regardless of the definer" (Kyro 2004) Adopting an interpretative, comparative concept analysis, Kyro (2004) suggests that benchmarking can be regarded as a special kind of action research. If so, the author affirms that, more attention should be put on "preliminary planning, observation, reflection and the use of theoretical frames".…”
Section: Discussionmentioning
confidence: 99%
“…'Companies should compare the best in class wherever it can be found' (McGaughy, 2002, p. 474), so other direct competitors in the same sector and other organizations synonymous with Internet activity, such as Amazon and Friends Reunited, were used as bases for comparison. Benchmarking is an established diagnostic tool to help improve an organization's performance (Kyro, 2004;O'Dell, 1994;Camp, 1989) and has developed to the extent of having an academic journal devoted to its discussion: Benchmarking; an International Journal. Benchmarking is seen as an appropriate research method to use in 'action research' (Kyro, 2004) as it is practitioner-focused and aims to offer potential improvements for an organization.…”
Section: Benchmarkingmentioning
confidence: 99%
“…Benchmarking is an established diagnostic tool to help improve an organization's performance (Kyro, 2004;O'Dell, 1994;Camp, 1989) and has developed to the extent of having an academic journal devoted to its discussion: Benchmarking; an International Journal. Benchmarking is seen as an appropriate research method to use in 'action research' (Kyro, 2004) as it is practitioner-focused and aims to offer potential improvements for an organization. We posit that it is also appropriate in 'business in action' research where the potential improvements are suggested but not necessarily implemented.…”
Section: Benchmarkingmentioning
confidence: 99%
“…This is mainly due to the developmental nature of both processes, and action research combines practical needs for developing performance and the collective intentional learning involved in it. As it contributes to an advanced understanding of the interplay between scientific and practical knowledge, action research can be used at the same time for both practical developmental work and scientific studies (Kyrö, 2004(Kyrö, , 2006. The action research methodology simultaneously strives to achieve useful outcomes for the benefit of the participants from practice and new forms of theoretical understanding.…”
Section: Research Scopementioning
confidence: 99%